THE CREATION OF “The Unseen Side of Sidoarjo” BOOK AS A COMMUNICATION MEDIA FOR SAVE STREET CHILD SIDOARJO COMMUNITY - Pratomo, Evan (VCD: Journal of Visual Communication Design, 2023)
The creation of "The Unseen Side of Sidoarjo" book as a communication media for Save Street Child Sidoarjo Community: Quality Education is point number 4 in the Sustainable Development Goals promoted by the United Nations. As a non-profit organization that cares for street children, Save Street Child (SSC) tried to reach out to cities in Indonesia until the emergence of the SSC Sidoarjo branch, which until now is still challenging to socialize concerns for street children in Sidoarjo city. Qualitative research will be conducted with field studies and primary and secondary data collection to gain a comprehensive understanding of the lives of street children in support of SSC Sidoarjo. This research will produce a documentary photo book that tells the stories of several Sidoarjo street children and information to support the SSC Sidoarjo community. Researchers designing "The Unseen Side of Sidoarjo"'s book found that combining photos with narrative, concept, and sequential content improves the delivery of social issues.